Menjawab Problematik Derajat Wanita Dalam Kehidupan Sosial Perspektif Fazlur Rahman - Faruq, Umar; Solehodin, Solehodin (Al-Hikmah: Jurnal Agama dan Ilmu Pengetahuan, 2025)
The theme of controversy regarding women has always been an interesting theme in Islamic studies. This made Fazlur Rahman also interested in studying it more deeply. This article explains in depth Fazlur Rahman's thoughts on polygamy. Fazlur Rahman has a different perspective on polygamy, this makes this theme even more interesting to read. This research is a literature review, prepared based on qualitative methods and analyzed descriptively. Islam came with a series of justifications for the actions carried out by the Arabs at that time. Through the Koran, Islam refutes negative accusations and stigma. Islam really glorifies women and the most important gender problem is answered through the concept of monotheism where the status of men and women are equal in the eyes of Allah and society.